Exploring refugees' experience of accessing dental health services in host countries: a scoping review - Asfari, Elaf; Rodriguez, Andrea; Dakessian, Arek; Yuan, Siyang (Frontiers in Oral Health, 2024)
Introduction: Refugees often face worse oral health outcomes, such as periodontal diseases and dental caries in host countries due to barriers including language and cultural differences, institutional discrimination, and restricted use of dental health services. This scoping review aims to map and summarise the available studies on refugees' experience of accessing dental health services in the host countries, to identify the main characteristics of the dental health services that refugees access and to explore the barriers and enablers to navigate the dental health service system in their host countries.Methods: The Joanna Briggs Institute (JBI) framework was adopted. PubMed, Scopus, Assia, CINAHL and Social Services Abstract were searched. A search strategy was developed using Medical Subject Headings (MeSH) terms and a combination of search operators and syntax used in MEDLINE were adopted for the remaining databases. Data were synthesised using thematic analysis.Results: Fourteen articles were included. Most studies used qualitative methods and Australia seemed to be the country with the highest number of publications surrounding this topic. The included studies showed that refugees frequently encountered substantial obstacles when attempting to access dental services in host countries. Numerous barriers such as language barriers, cultural differences, and lack of health insurance or financial support hindered refugees' ability to access these services. Additionally, many refugees possessed limited knowledge of the dental care system in their new country. As a result of untreated dental problems, refugees suffered from pain and other health complications.Discussion: This scoping review explored the challenges refugees have experienced in accessing dental health services in host countries, which included the key barriers such as affordability, accessibility, accommodation, availability, awareness, and acceptability. The scarcity of relevant research highlighted the need for a more comprehensive understanding of refugees' experiences accessing dental health services in host countries. Limited data were identified regarding evidence focusing on the characteristics of dental services accessed by refugees in host countries.